ANALISIS RENCANA INVESTASI AKTIVA TETAP TERHADAP PERLUASAN USAHA PADA PT. TASPI TRD COY DI KOTA MAKASSAR - Abdi, Sudirman (Idaarah: Jurnal Manajemen Pendidikan, 2017)
Investment plan undertaken by PT. Taspi TRD COY is an appropriate decision to improve its business. This policy is taken to compensate and meet consumer demand as well as to increase revenue. Based on the calculation of the analytical method used in assessing the feasibility of investment to be conducted by PT. Taspi TRD COY turned out to show the results of a positive calculation and declared eligible for immediate realized because it is considered to provide benefits for the company. Analysis of investment feasibility at PT. Taspi TRD COY can be used as a basis in assessing any proposed investment proposals. Result of calculation from Net Present Value method show positive result that is equal to Rp 676.859.406,8, -, or in other words fund equal to Rp 3,600,000,000, - can generate present value of cash flow equal to Rp 4,276,859,407, - which means this investment deserves to be accepted.